2006
DOI: 10.1620/tjem.208.117
|View full text |Cite
|
Sign up to set email alerts
|

Contribution of Plasma Matrix Metalloproteinases to Development of Left Ventricular Hypertrophy and Diastolic Dysfunction in Hypertensive Subjects

Abstract: Matrix metalloproteinases (MMPs) are involved in the regulation of the extracellular matrix (ECM) of the myocardium and thus the pathogenesis of vascular and cardiac hypertrophy. In this study, we investigated contribution of plasma matrix metalloproteinases to development of left ventricular hypertrophy (LVH) and diastolic dysfunction in hypertensive subjects. Hypertensive patients with (n = 27) and without LVH (n = 23) were included. All participants underwent a complete transthoracic echocardiographic exami… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
18
1
2

Year Published

2006
2006
2013
2013

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(21 citation statements)
references
References 18 publications
0
18
1
2
Order By: Relevance
“…These results contrast with studies in noninfectious settings, in which MMP-9 has been associated with maladaptive remodeling in both animal models and humans: MMP-9 levels are increased in the plasma of patients presenting with hypertension-induced hypertrophy 26 or congestive heart failure 27 and after ischemic attacks, 28 -30 which correlates with decreased cardiac function and adverse structural alterations. In light of these studies, it is apparent that MMP-9 plays a key role in innate immunity and clearance of cardiac infection, but it is also associated with cardiac injury.…”
Section: Discussioncontrasting
confidence: 82%
“…These results contrast with studies in noninfectious settings, in which MMP-9 has been associated with maladaptive remodeling in both animal models and humans: MMP-9 levels are increased in the plasma of patients presenting with hypertension-induced hypertrophy 26 or congestive heart failure 27 and after ischemic attacks, 28 -30 which correlates with decreased cardiac function and adverse structural alterations. In light of these studies, it is apparent that MMP-9 plays a key role in innate immunity and clearance of cardiac infection, but it is also associated with cardiac injury.…”
Section: Discussioncontrasting
confidence: 82%
“…Although not directly indicated in these studies, one can speculate that some of the MMP-2 induction occurs within the vascular endothelium; however, this requires more definitive investigation. Furthermore, other studies have demonstrated that cyclic strain-induced endothelial MMP-9 contributes to hypertensive remodeling in rats and humans (126).…”
Section: Cyclic Strain and Endothelial Dysfunction: Relevance To Vascmentioning
confidence: 98%
“…Med., a study by Saglam et al (2006) adds further weight to the hypothesis that plasma MMPs play a role in the development of LVH and diastolic dysfunction in hypertensive subjects. Their study group included 27 hypertensive patients with LVH and 23 without LVH; they found that plasma MMP-3 and Sundstrom et al (2004) TIMP-1 1069 Plasma TIMP-1 was positively associated with LV mass, wall thickness, relative wall thickness, end-systolic diameter, and LA diameter, increased LVEDD or wall thickness, and negatively correlated with fractional shortening.…”
mentioning
confidence: 99%
“…One previous study (Li-Saw-Hee et al 2000) explored the potential effects of treating hypertensive patients with an ACE-inhibitor or an ARB, albeit for a short period of time (about 2 months) and found no significant alteration in the MMP-9 and TIMP-1 levels, despite a fall in blood pressure (average treated blood pressure 143/85 mmHg). A follow up of the patients with LVH in the study by Saglam et al (2006), after treatment with an ACE-inhibitor or an ARB to assess for LVH regression as well as a fall in the MMP levels, that can be linked to a change in indices of diastolic dysfunction, would be interesting. Certainly, other short term treatment studies (Zervoudaki et al 2003) suggest that this may potentially be the case.…”
mentioning
confidence: 99%
See 1 more Smart Citation